Prostate Cancer Incidence Rates in Africa - Lisa W. Chu; Jamie Ritchey; Susan S. Devesa; Sabah M. Quraishi; Hongmei Zhang; Ann W. Hsing (Prostate Cancer, 2011)
African American men have among the highest prostate cancer incidence rates in the world yet rates among their African counterparts are unclear. In this paper, we compared reported rates among black men of Sub-Saharan African descent using data from the International Agency for Research on Cancer (IARC) and the National Cancer Institute Surveillance, Epidemiology, and End Results Program for 1973–2007. Although population-based data in Africa are quite limited, the available data from IARC showed that rates among blacks were highest in the East (10.7–38.1 per 100,000 man-years, age-adjusted world standard) and lowest in the West (4.7–19.8). These rates were considerably lower than those of 80.0–195.3 observed among African Americans. Rates in Africa increased over time (1987–2002) and have been comparable to those for distant stage in African Americans. These patterns are likely due to differences between African and African American men in medical care access, screening, registry quality, genetic diversity, and Westernization. Incidence rates in Africa will likely continue to rise with improving economies and increasing Westernization, warranting the need for more high-quality population-based registration to monitor cancer incidence in Africa.